Effectiveness of Contextual Teaching Strategies in Enhancing Civic Attitudes of Islamic Elementary School Students - Muhamad Acsal; Mustafa Habib (Journal of Contemporary Islamic Primary Education, 2025)
This study investigates the effectiveness of contextual teaching and learning (CTL) strategies in enhancing civic attitudes among students at Madrasah Ibtidaiyah (Islamic Elementary Schools). The research was motivated by the persistent gap between civic knowledge and actual civic behavior observed in elementary-level learners, which indicates the need for more meaningful and experience-based learning approaches. The objective of this study is to explore how CTL strategies contribute to the development of civic attitudes through real-life contextualization of learning materials. Employing a qualitative approach with a case study design, the research was conducted at a Madrasah Ibtidaiyah in Kendari, Indonesia. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using an interactive model involving data condensation, data display, and conclusion drawing. The findings reveal that contextual learning fosters students’ active participation, strengthens value internalization, and improves civic behaviors such as tolerance, social responsibility, and democratic engagement. These results imply that CTL is an effective pedagogical strategy for character-building in civic education, particularly within religious-based elementary institutions. The study recommends broader implementation of CTL in civic instruction and further research to evaluate its long-term impact on students’ character development.